The preoperative neutrophil-to-lymphocyte ratio predictive value for survival in patients with brain metastasis - Picarelli, Helder; Yamaki, Vitor Nagai; Solla, Davi Jorge Fontoura; Neville, Iuri Santana; Santos, Alexandra Gomes dos; Freitas, Bruno Spindola Amaral Garcia de; Diep, Calvin; Paiva, Wellingson Silva; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos de Neuro-Psiquiatria, 2022)
Background The neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) have been previously studied as predictors of survival in different malignancies.Objective The aim of this study was to evaluate the predictive value of these hematologic inflammatory biomarkers for patients with brain metastases (BM).Methods We reviewed a consecutive cohort of patients at Instituto do Cancer do Estado de São Paulo (ICESP-FMUSP) from 2011 to 2016 with ≥ 1 BM treated primarily by surgical resection. The primary outcome was 1-year survival. We optimized the NLR, MLR, PLR, and RDW cutoff values, preserving robustness and avoiding overestimation of effect size.Results A total of 200 patients (mean age 56.1 years; 55.0% female) met inclusion criteria. Gross-total resection was achieved in 89.0%. The median (quartiles) preoperative and postoperative KPS scores were 60 (50–80) and 80 (60–90), respectively. Preoperative NLR was significantly associated with survival (HR 2.66, 95% CI: 1.17–6.01, p = 0.019). A NLR cutoff value of 3.83 displayed the most significant survival curve split.Conclusions Preoperative NLR is an independent predictor of survival in newly diagnosed BM. We propose a cutoff value of 3.83 for preoperative NLR testing may be clinically useful as predictor of poor survival in this population. The wide accessibility of the NLR favors its inclusion in clinical decision-making processes for BM management.
Keywords: Brain Neoplasms; Survival Analysis; Biomarkers